The Effect Of The Implementation Of Corporate Social Responsibility, Profitability And Corporate Value On Tax Aggressiveness At Pt Younexa Inti Material Cikarang - Tedi Setiawan; Agus Subagiyo (LP2M IAIN Palopo, 2026)
This research was conducted to test and analyze the influence of the implementation of corporate social responsibility, profitability and corporate value on tax aggressiveness. The population in this study is PT. Younexa Inti Material Cikarang, The sampling method used was snowball sampling, so that 129 samples were obtained. This research uses a quantitative approach with the type of associative research This research also uses secondary data obtained from the website of PT. Younexa Material Core Cikarang. The statistical method used to test the research hypothesis was multiple linear regression analysis with the help of SPSS 23.0 software. The results of this study prove that the implementation of corporate social responsibility has no effect on tax aggressiveness. Then the results of the T test and the F test prove that the application of profitability has an effect on tax aggressiveness, and the application of company values has no effect on tax aggressiveness.